2011
DOI: 10.1177/0042098011415718
|View full text |Cite
|
Sign up to set email alerts
|

New Supply and Price Dynamics in the Singapore Housing Market

Abstract: In this paper, VAR models are employed to trace the price response of existing houses to the quantity of new units launched by homebuilders in Singapore between 1996 and 2009. Contrary to the 'competition' hypothesis prediction of a negative reaction, it is found that marginal supply Granger-cause existing house prices in a positive manner. The effect is robust to the inclusion of exogenous demand factors as well as price interaction in the primary (new houses) and secondary (existing houses) market segments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…It is a measure of the responsiveness of housing supply to change in housing price. Housing supply elasticity plays an important role in explaining the evolution of housing price (Blackley, 1999;Glaeser, Gyourko, & Saks, 2006;Malpezzi & Maclennan, 2001;Ooi & Le, 2012;Pryce, 1999). Positive demand shocks caused by population growth, income increase or the decline in mortgage interest rate can put upward pressure on housing price.…”
Section: Housing Supply Elasticitymentioning
confidence: 99%
“…It is a measure of the responsiveness of housing supply to change in housing price. Housing supply elasticity plays an important role in explaining the evolution of housing price (Blackley, 1999;Glaeser, Gyourko, & Saks, 2006;Malpezzi & Maclennan, 2001;Ooi & Le, 2012;Pryce, 1999). Positive demand shocks caused by population growth, income increase or the decline in mortgage interest rate can put upward pressure on housing price.…”
Section: Housing Supply Elasticitymentioning
confidence: 99%
“…Rapid inflation does cause large increases in the cost of materials and land (Noppen 2012). Ooi and Le (2012) used Vector Autoregressive (VAR) models to trace the price response of existing houses to the quantity of new units launched by homebuilders in Singapore between 1996 and 2009. They found that contrary to the "competition" hypothesis prediction of a negative reaction, they found that marginal supply Granger-cause existing house prices in a positive manner.…”
Section: Effect Of Economic Factors On Funding Of Housingmentioning
confidence: 99%
“…Ooi et al looked at Singapore between 1996 and 2009 and traced the price response of existing houses to the quantity of new units launched by home builders [8]. Malpezzi et al estimated the price elasticity of the housing supply from new construction separately in the United States and in the United Kingdom [9].…”
Section: Literature Reviewmentioning
confidence: 99%